A roadmap for the Australian space industry to contribute to global societal challenges - Flentje, Warren; Clayfield, Kimberley; Held, Alexander; Pearce, Sarah; Crosby, Philip (2018)
The Australian Space Agency was established on 1 July 2018 with a mission to grow the Australian space industry with a focus on opportunity areas including Earth observation, communications, enhanced positioning and situational awareness. Space-derived services particularly in these fields offer powerful tools for combating global societal challenges. Australia faces many challenges relevant to space-derived services including communications and managing industry and ecosystems over vast distances. In developing new solutions using space-based communications, Earth observation and enhanced positioning, Australia can make a significant contribution to global challenges. Australia also offers an excellent location for tracking space objects including space debris and threats from Near Earth Objects. A new Roadmap from the national science agency introduces some major opportunity themes consistent with the Agency’s priority areas, along with technology developments in each - enabling business, research and infrastructure investments that can contribute to progress. Examples are given where space-derived services are making a significant contribution to global societal challenges. While the opportunities identified in the Roadmap align to the Agency priority areas they are independently assessed and do not necessarily represent the views of the Agency.